(3aGFOI UhQI aJhi egeI aj ci GdMeUIs - (3Ydj GdSHQGedjs
(3ChdgG (B:s
(3aGFOI UhQI aJhi egeI ai ci GdMeUI QaYJ dehdGfG Ydi GdSHQGedi ai ci jJYGWhfg HOeTb GdTGe s
(3BNQgG (B:s
(3hGdca Yf GdeYGUi HZjI GdJbQH TQW ai GdKhGH GfJgi CTHGg GdSjhWi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
Keywords: (3GdeLGejYs